Juliusz Bardach, Stanisław Grodziski, Andrzej Gwiżdż, Adam Jankiewicz, Kazimierz Działocha, Romuald Kraczkowski, Dariusz Jarosz, Dzieje Sejmu Polskiego, 1933 - Olszewski, Henryk (Czasopismo Prawno-Historyczne, 1993)
Recenzja: Juliusz Bardach, Stanisław Grodziski, Andrzej Gwiżdż, Adam Jankiewicz, Kazimierz Działocha, Romuald Kraczkowski, Dariusz Jarosz. Koordynator pracy: Juliusz Bardach, Dzieje Sejmu Polskiego, Wydawnictwo Sejmowe, Warszawa 1993, s. 399.